Substituted heteropolyacid catalysts for aldol condensation reactions, their preparation and applications
By introducing other metals in the absence of Keggin type heteropoly acid, an efficient substituted heteropoly acid catalyst was prepared, which solved the problems of low activity and poor selectivity of existing catalysts in water environments, and achieved methacrylic acid High-efficiency catalysis and production of methyl esters.
Patent Information
- Application Number
- CN202111519540.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-12-13
AI Technical Summary
The existing aldol condensation reaction catalysts have low activity and poor selectivity in water environments, resulting in high production costs and serious pollution of methyl methacrylate, which makes it difficult to be promoted in industrialization.
A substituted heteropolyacid catalyst is prepared by introducing other metals into its absence, and a replacement heteropolyacid catalyst is improved through specific preparation methods and reaction conditions.
The catalyst has a bifunctional active center, which has strong activity and good selectivity, and can effectively catalyze the aldol condensation reaction between methanol and methyl propionate, improving the conversion and selectivity of methyl methacrylate.
Smart Images

Figure GDA0003597498610000041
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method and application of a substituted heteropoly acid catalyst for aldol condensation reaction, and in particular to a preparation method of a Keggin type heteropoly acid catalyst for aldol condensation reaction by introducing other metals at the vacancy of the heteropoly acid and a method for preparing methyl methacrylate by catalyzing a mixed solution (or mixed aqueous solution) of methanol and methyl propionate. Background Art
[0002] Methyl methacrylate (MMA) is an important organic chemical raw material, mainly used to produce organic glass (polymethyl methacrylate, PMMA), and also used to manufacture other resins, plastic PVC impact modifiers, coatings, wood and cork impregnation agents, motor coil impregnation agents and insulation potting materials and other industrial uses. In 2020, the global methyl methacrylate market size reached 51.4 billion yuan, and is expected to reach 64.9 billion yuan in 2026, with a compound annual growth rate (CAGR) of 3.4%.
[0003] From the perspective of raw materials, the production methods of MMA can be divided into: acetone cyanohydrin method (ACH method), C2, C3 and C4 route methods. At present, the domestic MMA production process is mainly the ACH method, which has high production costs and serious pollution. The Alpha method is a new green production process route, which is mainly divided into two steps. First, ethylene is carbonylated to synthesize methyl propionate, and then methyl propionate and formaldehyde are condensed to synthesize MMA. It has the characteristics of easy availability of raw materials, safety, environmental friendliness and no pollution. This series of catalysts has also been widely studied, such as reported in patents CN201410784248, CN201210276200, CN 201810925782, CN 201910368812, CN201110212068, EP 0710643, US Pat. No. 4,618,709, and US Pat. No. 4,956,493. However, the formaldehyde sources used in this series of catalysts are mostly methylal, trioxymethylene or polyformaldehyde dissolved in methanol. However, the generation of water is inevitable in the aldol condensation reaction, which can easily cause hydrolysis of raw materials and products and deactivation of catalysts, leading to problems such as low catalyst activity and poor selectivity. Although some studies have proposed carrier modification or adding a small amount of water-resistant additives to improve the water resistance of the catalyst, the effect is not very obvious, so it has been difficult to promote and utilize industrially. Summary of the invention
[0004] The main technical problem solved by the present invention is to provide a method for preparing a catalyst for aldol condensation reaction by introducing other metals at the vacancy of Keggin type heteropoly acid and a method for preparing methyl methacrylate by catalyzing a mixed solution (or a mixed aqueous solution) of methanol and methyl propionate.
[0005] A preparation method and application of a substituted heteropolyacid catalyst for aldol condensation reaction, specifically:
[0006] Preparation of substituted heteropolyacid catalysts for aldol condensation reaction:
[0007] A substituted heteropolyacid catalyst for aldol condensation reaction, the chemical formula of which is H n [Z a+ (H2O)X b+ W 11 O 39 ]·mH2O / SiO2(XW 11 Z / S), wherein the substituent metal Z is one of Fe, Cr, Al, Ni, Si, Zn, Cs, V, and La; X is one of metals Fe, Ni, Ti, Zn, V, and Cs; wherein the molar ratio of the substituent metal X: the substituent metal Z: the central atom W is 1:1:11;
[0008] The substituted metal X and the substituted metal Z are the same or different; wherein m is an integer of 1, n+a+b=12, a and b are the valence states of the corresponding elements, and n, a and b are integers.
[0009] The substituted metal Z is one or more of nitrates, carbonates or acetates of Fe, Cr, Al, Ni, Si, Zn, Cs, V and La.
[0010] The substituted metal X is one or more of nitrates, carbonates or acetates of Fe, Ni, Ti, Zn, V and Cs.
[0011] Calculated on the basis of carrier SiO2, the mass fraction of heteropoly acid in the catalyst is 5-50wt%.
[0012] The present invention provides a specific method for preparing the above-mentioned catalyst for aldol condensation reaction, comprising:
[0013] (1) Weigh 10-50 g of Na2WO4·2H2O and add it to deionized water at 50-70° C. to form a 0.1-1 mol / L aqueous solution, adjust the pH of the solution to 3-7 with 30-80 wt % acetic acid or 1-30 wt % hydrochloric acid, and then heat the solution to boiling;
[0014] (2) Weigh a certain amount of salt containing element X, add it to 50-70° C. deionized water to form a 0.1-2 mol / L aqueous solution, then add the solution to solution (1) while stirring, and stir for 30-120 min.
[0015] (3) Weigh a certain amount of salt containing element Z, add it to 50-70° C. deionized water to form a 0.1-2 mol / L aqueous solution, then add the solution to solution (2), adjust the pH of the solution to 2-6 with 30-99wt% acetic acid or 1-30wt% hydrochloric acid, and continue stirring. During the stirring process, continuously add water and maintain the pH value at about 2-6. Stop stirring after 1.5 hours.
[0016] (4) After the solution (3) is cooled, anhydrous ethanol in an amount equal to the volume of all metal salt solutions is added to obtain a product, which is transferred into a separatory funnel, and 20-100 ml of ether is added and fully shaken to extract and separate the product. After shaking, the extract phase is a mixture of heteropoly acid and ether located at the bottom layer of the solution, and the raffinate phase is a heteropoly acid mixed aqueous solution remaining after extraction located at the upper layer of the solution. The raffinate phase is added with ether and extracted 1-5 times repeatedly, and the extract phase is dissolved in 50-200 ml of water, and the solution is transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1.
[0017] (5) Weigh a certain amount of carrier SiO2 and add it to the prepared solution (4). After fully mixing, filter out excess water, dry at 80-150°C for 1-6 hours, and calcine at 300-800°C for 1-10 hours to obtain a substituted heteropoly acid catalyst XW for aldol condensation reaction. 11 Z / S;
[0018] This series of catalysts can be used to prepare methyl methacrylate through aldol condensation reaction of a mixed solution of methanol and methyl propionate or a mixed solution containing water thereof.
[0019] A fixed bed reactor is used, the aldol condensation reaction catalyst is filled in the middle of the bed (the catalyst is selected to be 20-100 mesh after molding), and the upper and lower sections are filled with quartz sand; the raw material is a mixed solution of methanol and methyl propionate or a water-containing mixed solution thereof; the reaction temperature is 200-450° C., the pressure is 0.05-2MPa, and the LHSV of the reaction process is 0.1-3h -1 The product that can be collected is a mixed solution containing methyl methacrylate and methacrylic acid.
[0020] The molar ratio of methanol:methyl propionate:oxygen in the mixed solution of methanol and methyl propionate or its aqueous mixed solution is 1:(0.2-3):(0.2-0.7), and the water content is 0-60wt%.
[0021] The reaction involved in the present invention can be represented by the following reaction equation:
[0022]
[0023] The catalyst of the invention has a bifunctional active center, strong activity, good selectivity and the like.
[0024] Beneficial technical effects of the present invention:
[0025] 1. The prepared heteropoly acid is a heteropoly acid with a Keggin-type structure, and its primary structure is a weak base, so the catalyst has certain acid-base active sites, its reaction conditions are mild, and its stability is good;
[0026] 2. The catalyst has good stability and activity. The reaction system is a mixed solution of methanol and methyl propionate or a mixed solution containing water. Based on methyl propionate, the highest conversion rate of methyl propionate is 24.30%, the highest selectivity of methyl methacrylate is 87.60%, and the highest comprehensive yield of methyl methacrylate and methacrylic acid is 25.68%. DETAILED DESCRIPTION
[0027] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.
[0028] Example 1
[0029] Weigh 25gNa2WO4·2H2O, add it to 50℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.3 with 45wt% acetic acid, and then heat it to boiling, recorded as solution A; weigh 4.04g Fe(NO3)3·9H2O, add it to 50℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution A while stirring, stir for 30min, recorded as solution B; weigh 1.19g NiCO3, add it to 50℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution B, add 75wt% acetic acid to adjust the pH to 5.0 and continue stirring, continuously add water during the stirring process, and maintain the pH value at 5.0, stop stirring after 1.5h, recorded as solution C. After solution C was cooled to room temperature, 237.80 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 40 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted three times. The extract phase (the mixture of heteropolyacid and ether) was dissolved in 100 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1, and the obtained heteropoly acid was H7Fe(H2O)NiW 11 O 39 ·8H2O, recorded as D.
[0030] Weigh 20g of carrier SiO2 and add it to the prepared solution D, and continue stirring for 6h under the action of magnetic stirring; then filter it, dry it at 120℃ for 6h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 6h. The obtained sample is the catalyst for producing methyl methacrylate, which is denoted as FeW 11 Ni / S;
[0031] The obtained sample was pressed into a 40-60 mesh size and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The aldol condensation reaction catalyst was filled into the middle section of the bed, and the upper and lower sections of the catalyst bed were filled with quartz sand respectively; the raw material was a mixed solution of methanol and methyl propionate, the molar ratio of methanol: methyl propionate: oxygen was 1:1:0.5, the reaction temperature was 340°C, the pressure was 0.20MPa, the residence time was 4s, and the raw material LHSV was 3h -1 The carrier gas was an oxygen-containing inert atmosphere (O2 content 5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 20.10%, and the selectivity of methyl methacrylate was 76.1%.
[0032] Example 2
[0033] Weigh 35g Na2WO4·2H2O, add it to 50℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.0 with 60wt% acetic acid, and then heat it to boiling, record it as solution A; weigh 1.19g NiCO3, add it to 50℃ deionized water to form a 0.2mol / L aqueous solution, then add the solution to solution A while stirring, stir for 30min, record it as solution B; weigh 1.90g TiCl4, add it to high-temperature deionized water to form a 0.2mol / L aqueous solution, then add the solution to solution B, add 85wt% acetic acid to adjust the pH to 5.0 and continue stirring, continuously add water during the stirring process, and maintain the pH value at about 5.0, stop stirring after 1.5h, record it as solution C. After solution C was cooled to room temperature, 292.93 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 70 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted three times. The extract phase (the mixture of heteropolyacid and ether) was dissolved in 200 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1. The obtained heteropoly acid was H6Ni(H2O)TiW 11 O 39 ·9H2O, recorded as D.
[0034] Weigh 20g of carrier SiO2 and add it to the prepared solution D, and continue stirring for 6h under the action of magnetic stirring; then filter it, dry it at 120℃ for 3h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 6h. The obtained sample is the catalyst for producing methyl methacrylate, denoted as NiW 11 Ti / S;
[0035] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1:1.5:0.5, the reaction temperature was 340°C, the pressure was 0.05 MPa, the residence time was 4 s, and the LHSV was 3 h. -1 The carrier gas was an oxygen-containing inert atmosphere (O2 content 5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 16.50%, and the selectivity of methyl methacrylate was 63.20%.
[0036] Example 3
[0037] Weigh 25g Na2WO4·2H2O, add it to 60℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.3 with 45wt% acetic acid, and then heat it to boiling, record it as solution A; weigh 2.38g Cr(NO3)3, add it to 60℃ deionized water to form a 0.2mol / L aqueous solution, then add the solution to solution A while stirring, stir for 30min, record it as solution B; weigh 1.17g NH4VO3, add it to 60℃ deionized water to form a 0.2mol / L aqueous solution, then add the solution to solution B, adjust the pH to 5.0 with 90wt% acetic acid and continue stirring, continuously add water during stirring, and maintain the pH value at about 5.0, stop stirring after 1.5h, record it as solution C. After solution C was cooled to room temperature, 237.80 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 60 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted three times. The extract phase (the mixture of heteropolyacid and ether) was dissolved in 150 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1, and the obtained heteropoly acid was H4Cr(H2O)VW 11 O 39 ·16H2O, denoted as D.
[0038] 20 g of carrier SiO2 was weighed and added to the prepared solution D, and stirred continuously for 6 h under the action of magnetic stirring; then filtered, dried at 120 ° C for 6 h, and finally calcined in a muffle furnace at 500 ° C in air atmosphere for 6 h. The obtained sample was the catalyst for producing methyl methacrylate, denoted as CrW 11 V / S;
[0039] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1:1:0.5, the reaction temperature was 360°C, the pressure was 0.05 MPa, the residence time was 4 s, and the LHSV was 2 h. -1 The carrier gas was an oxygen-containing inert atmosphere (O2 content 3.5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 17.20%, and the selectivity of methyl methacrylate was 73.10%.
[0040] Example 4
[0041] Weigh 45g Na2WO4·2H2O, add it to 60℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.0 with 70wt% acetic acid, and then heat it to boiling, record it as solution A; weigh 3.75g Al(NO3)3·9H2O, add it to 60℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution A while stirring, stir for 30min, record it as solution B; weigh 1.17g NH4VO3, add it to 60℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution B, adjust the pH to 5.0 with 40wt% acetic acid and continue stirring, continuously add water during stirring, and maintain the pH value at about 5.0, stop stirring after 1.5h, record it as solution C. After solution C was cooled to room temperature, 348.05 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 80 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted 4 times. The extract phase (the mixture of heteropolyacid and ether) was dissolved in 200 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1, and the obtained heteropoly acid was H4Al(H2O)VW 11 O 39 ·22H2O, recorded as D.
[0042] Weigh 20g of carrier SiO2 and add it to the prepared solution D, and continue stirring for 6h under the action of magnetic stirring; then filter it, dry it at 120℃ for 1h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 6h. The obtained sample is the catalyst for producing methyl methacrylate, denoted as AlW 11 V / S;
[0043] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1:1.5:0.2, the reaction temperature was 360°C, the pressure was 0.10 MPa, the residence time was 4 s, and the LHSV was 2 h. -1 The carrier gas was an oxygen-containing inert atmosphere (O2 content 2.5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 13.80%, and the selectivity of methyl methacrylate was 76.30%.
[0044] Example 5
[0045] Weigh 25g Na2WO4·2H2O, add it to 70℃ deionized water to form a 1mol / L aqueous solution, then heat it to boiling, slowly drop 21ml of 15wt% hydrochloric acid into the solution under stirring, record it as solution A; weigh 2.75g Na2SiO3·9H2O, add it to 70℃ deionized water to form a 0.2mol / L aqueous solution, then quickly add the solution into solution A, drop 15wt% hydrochloric acid solution into the solution to keep the pH at about 5.5, boil it for 1h and then cool it to room temperature, record it as solution B; then add 12.52g KCl into solution B, wash it with cold water and filter it, the obtained heteropoly acid is K8SiW 11 VO 39 ·13H2O, recorded as C.
[0046] Weigh 20g of carrier SiO2 and add it to the prepared solution C, and continue stirring for 6h under the action of magnetic stirring; then filter it, dry it at 120℃ for 6h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 6h. The obtained sample is the catalyst for producing methyl methacrylate, recorded as KW 11 Si / S;
[0047] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1:0.5:0.6, the reaction temperature was 360°C, the pressure was 0.05 MPa, the residence time was 4 s, and the LHSV was 1.5 h. -1The carrier gas was an oxygen-containing inert atmosphere (O2 content 5.0 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 18.40%, and the selectivity of methyl methacrylate was 86.10%.
[0048] Example 6
[0049] Weigh 25g Na2WO4·2H2O, add it to 65℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.5 with 35wt% acetic acid, and then heat it to boiling, recorded as solution A; weigh 1.89g Zn(NO3)2, add it to 65℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution A while stirring, stir for 30min, recorded as solution B; weigh 1.17g NH4VO3, add it to high-temperature deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution B, adjust the pH to 5.0 with 90wt% acetic acid and continue stirring, continuously add water during stirring, and maintain the pH value at about 5.0, stop stirring after 1.5h, recorded as solution C. After solution C was cooled to room temperature, 237.80 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 100 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted twice, and the extract phase (the mixture of heteropolyacid and ether) was dissolved in 150 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1, and the obtained heteropoly acid was H5Zn(H2O)VW 11 O 39 ·11H2O, denoted as D.
[0050] Weigh 20g of carrier SiO2 and add it to the prepared solution D, and continue stirring for 6h under the action of magnetic stirring; then filter it, dry it at 120℃ for 5h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 6h. The obtained sample is the catalyst for producing methyl methacrylate, which is denoted as ZnW 11 V / S;
[0051] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1: 0.2: 0.7, the reaction temperature was 360°C, the pressure was 0.15 MPa, the residence time was 10 s, and the LHSV was 3 h. -1The carrier gas was an oxygen-containing inert atmosphere (O2 content 1.5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 6.80%, and the selectivity of methyl methacrylate was 43.20%.
[0052] Example 7
[0053] Weigh 25g Na2WO4·2H2O, add it to 60℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.0 with 70wt% acetic acid, and then heat it to boiling, recorded as solution A; weigh 3.26g Cs2CO3, add it to high-temperature deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution A while stirring, and stir for 30min, recorded as solution B; weigh 1.17g NH4VO3, add it to high-temperature deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution B, adjust the pH to 5.0 with 60wt% acetic acid, and continue stirring. During the stirring process, continuously add water and maintain the pH value at about 5.0. Stop stirring after 1.5h, recorded as solution C. After solution C was cooled to room temperature, 237.80 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 90 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted 4 times, and the extract phase (the mixture of heteropolyacid and ether) was dissolved in 150 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1, and the obtained heteropoly acid was H6Cs(H2O)VW 11 O 39 ·11H2O, denoted as D.
[0054] Weigh 20g of carrier SiO2 and add it to the prepared solution D, and continue stirring for 3h under the action of magnetic stirring; then filter it, dry it at 120℃ for 6h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 8h. The obtained sample is the catalyst for producing methyl methacrylate, which is denoted as CsW. 11 V / S;
[0055] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1:3:0.4, the reaction temperature was 340°C, the pressure was 0.15 MPa, the residence time was 10 s, and the LHSV was 3 h. -1The carrier gas was an oxygen-containing inert atmosphere (O2 content 4.5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 23.50%, and the selectivity of methyl methacrylate was 85.20%.
[0056] Example 8
[0057] Weigh 35g Na2WO4·2H2O, add it to 50℃ deionized water to form a 0.55mol / L aqueous solution, adjust the pH of the solution to 6.3 with 30wt% acetic acid, and then heat it to boiling, recorded as solution A; weigh 4.04g Fe(NO3)3·9H2O, add it to 50℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution A while stirring, stir for 30min, recorded as solution B; weigh 3.26g Cs2CO3, add it to 50℃ deionized water to form a 0.2mol / L aqueous solution, and then add the solution to solution B, adjust the pH to 4.0 with 99wt% acetic acid and continue stirring, continuously add water during the stirring process, and maintain the pH value at about 4.0, stop stirring after 1.5h, recorded as solution C. After solution C was cooled to room temperature, 292.93 ml of anhydrous ethanol was added to obtain the product, which was transferred to a separatory funnel, and 100 ml of ether was added and fully shaken to extract and separate the product. The raffinate phase (the heteropolyacid mixed aqueous solution remaining after extraction) was added with ether and extracted three times, and the extract phase (the mixture of heteropolyacid and ether) was dissolved in 200 ml of water, and the solution was transferred to H + The solution was repeatedly ion exchanged in an Amberlite IR-120 cation exchange column until the pH was <1, and the obtained heteropoly acid was H8Fe(H2O)CsW 11 O 39 ·8H2O, recorded as D.
[0058] Weigh 20g of carrier SiO2 and add it to the prepared solution D, and continue stirring for 6h under the action of magnetic stirring; then filter it, dry it at 120℃ for 1h, and finally calcine it in a muffle furnace at 500℃ in air atmosphere for 3h. The obtained sample is the catalyst for producing methyl methacrylate, which is denoted as FeW 11 Cs / S;
[0059] The obtained sample was pressed into 40-60 mesh and then loaded into a stainless steel tube fixed bed reactor (fixed bed inner diameter 8 mm). The molar ratio of methanol: methyl propionate: oxygen was 1:3:0.6, the reaction temperature was 360°C, the pressure was 0.15 MPa, the residence time was 10 s, and the LHSV was 3 h. -1The carrier gas was an oxygen-containing inert atmosphere (O2 content 4.5 vol%), and the inert gas was N2. Gas chromatography was used for online monitoring; the final analysis showed that the conversion rate of methyl propionate was 24.30%, and the selectivity of methyl methacrylate was 87.60%.
[0060] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A substituted heteropolyacid catalyst for aldol condensation reaction, characterized in that: Its chemical formula is H n [Z a+ (H2O)X b+ W 11 O 39 ]·mH2O / SiO2, the simplified formula is XW 11 Z / S, wherein the substituent metal Z is one of Fe, Cr, Al, Ni, Si, Zn, Cs, V, and La; X is one of Fe, Ni, Ti, Zn, V, and Cs; wherein the molar ratio of the substituent metal X: the substituent metal Z: the central atom W is 1:1:11; and the substituent metal X and the substituent metal Z are the same or different; wherein m is an integer of 1, n+a+b=12, a and b are the valence states of the corresponding elements, and n, a, and b are integers, The preparation method of the catalyst comprises the following steps: (1) Weigh 10-50 g Na2WO4·2H2O and add it to 50-70 ℃ deionized water to form a 0.1-1 mol / L aqueous solution. Adjust the pH of the solution to 3-7 with 30-80 wt% acetic acid or 1-30 wt% hydrochloric acid, and then heat the solution to boiling; (2) Weigh a salt containing element X and add it to 50-70 °C deionized water to form a 0.1-2 mol / L aqueous solution, then add the solution to the solution in step (1) while stirring, and stir for 30-120 min; (3) Weigh a salt containing the Z element and add it to 50-70°C deionized water to form a 0.1-2 mol / L aqueous solution, then add the solution to the solution in step (2), adjust the pH of the solution to 2-6 with 30-99 wt% acetic acid or 1-30 wt% hydrochloric acid, and continue stirring. During the stirring process, water is continuously added to maintain the pH value at 2-6. Stirring is stopped after 0.5-3 hours; (4) After the solution of step (3) is cooled to room temperature, anhydrous ethanol in an equal volume to the total volume of the metal salt solution is added to obtain a product, the product is transferred to a separatory funnel, 20-100 ml of ether is added and the product is fully shaken to extract and separate the product. After shaking, the extract phase is a mixture of heteropoly acid and ether located at the bottom layer of the solution, and the raffinate phase is a heteropoly acid mixed aqueous solution remaining after extraction located at the upper layer of the solution. The raffinate phase is added with ether and the extraction is repeated 1-5 times. The extract phase is dissolved in 50-200 ml of water, and the solution is transferred to H + In the AmberliteIR-120 cation exchange column, the solution is repeatedly ion exchanged until the pH is <1; (5) Weigh the carrier SiO2 and add it to the prepared solution of step (4). After fully mixing, filter out the excess water and dry at 80-150°C for 1-6 hours. Then, calcine in air at 300-800°C for 1-10 hours to obtain the substituted heteropoly acid catalyst XW for aldol condensation reaction. 11 Z / S.
2. The catalyst according to claim 1, characterized in that Calculated on the carrier SiO2, the mass fraction of the heteropoly acid in the catalyst is 1-50wt%.
3. The catalyst according to claim 2, characterized in that: Calculated on the carrier SiO2, the mass fraction of the heteropoly acid in the catalyst is 5-30wt%.
4. The catalyst according to claim 3, characterized in that: The salt containing the Z element is one or more of the nitrates, carbonates or acetates of Fe, Cr, Al, Ni, Si, Zn, Cs, V and La; the salt containing the X element is one or more of the nitrates, carbonates or acetates of Fe, Ni, Ti, Zn, V and Cs.
5. Use of the catalyst according to any one of claims 1 to 4, characterized in that: The catalyst is used for catalyzing a mixed solution of methanol and methyl propionate, or a water-containing mixed solution of methanol and methyl propionate to prepare methyl methacrylate through an aldol condensation reaction.
6. The use of the catalyst according to claim 5, characterized in that: A fixed bed reactor is used, the aldol condensation reaction catalyst is filled in the middle of the bed, the catalyst is selected to be 20-100 mesh after molding, and the upper and lower sections of the catalyst bed are filled with quartz sand respectively; the raw material is a mixed solution of methanol and methyl propionate or a water-containing mixed solution thereof, and an oxygen-containing inert atmosphere is used as a carrier gas; the reaction temperature is 200-450°C, the pressure is 0.05-2MPa, and the LHSV of the raw material during the reaction is 0.1-3 h -1 ; The product that can be collected is a mixed solution containing methyl methacrylate and methacrylic acid.
7. The use of the catalyst according to claim 6, characterized in that: The molar ratio of methanol:methyl propionate:oxygen in the mixed solution of methanol and methyl propionate or its aqueous mixed solution is 1:(0.2-3):(0.2-0.7), and the water content is 0-60 wt%; the carrier gas is an oxygen-containing inert atmosphere, wherein the O2 content is 1-5 vol% and the rest is N2.
Citation Information
Patent Citations
Zr-Cs series methyl methacrylate catalyst added with modification auxiliary agent and preparation method thereof
CN102350336A
A method for preparing methyl methacrylate from methyl propionate and formaldehyde
CN102775302B
Method for producing methyl methacrylate by methyl acetate and formaldehyde
CN104513163A
Polymer modified supported metal catalyst and preparation method and application thereof
CN109225192A
Acid-base bifunctional catalyst for synthesis of methyl methacrylate by methyl propionate and formaldehyde
CN109999922A